Comprehensive Study of the Influence of the Bonding Temperature and Contact Pressure Regimes during Diffusion Bonding on the Deformation and Mechanical Properties of AISI 304. Issue 8 (7th May 2021) - Gietzelt, Thomas; Walter, Mario; Toth, Volker; Messerschmidt, Florian; Blem, Melina
Abstract : Process parameters for diffusion bonding are temperature, dwell time, and contact pressure. Temperature and contact pressure have opposite effects on deformation. The effect of temperature on deformation was investigated in steps of 20 K from 1015 to 1135 °C. Contact pressure and dwell time were 16 MPa and 4 h, respectively. The deformation increase steadily with temperature. Yield strength and tensile strength decrease slightly with temperature, which is attributed to grain growth. The elongation‐at‐fracture values are 100–105%. For 925 to 995 °C, values for elongation at fracture decrease. It was investigated if comparable mechanical properties can be obtained at a temperature of 850 °C only. Experiments with higher constant contact pressures were supplemented by tests with superimposed short load peaks. Similar and higher values for the yield strength were achieved. A correlation of yield strength, tensile strengths and elongation‐at‐fracture values with contact pressure and contact pressure regime was found. The values for elongation at fracture are significantly lower than those for higher temperatures. This even applies to parameter sets at different temperatures, leading to almost identical deformations. Reduced elongation‐at‐fracture values at 850 °C are attributed to microscopically small defects in the bonding plane and to notch effects. Abstract : The article evaluates the relation between deformation and mechanical properties for diffusion bonding of austenitic stainless steel AISI 304 for a temperature range of 800–1135 °C and contact pressures from 16 to 64 MPa. The mechanical properties cannot be directly deduced from deformation values. For deformation control, the approach of short‐term peak loading is proposed.